A search for invisible Higgs bosons produced in e(+)e(-) interactions at LEP 2 energies - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (1999)
Searches for HZ production with the Higgs boson decaying into an invisible final state have been performed with the data collected by the DELPHI experiment up to the centre-of-mass energy of 183 GeV. The hadronic and muon pair final states of the Z boson were analysed. From the absence of signal, upper limits on the cross-section and the corresponding Higgs boson mass limits were set at 95% confidence level. The results are interpreted as excluded parameter regions in the framework of the minimal supersymmetric standard model and in the simplest Majoron model with one Higgs doublet and one Higgs singlet field. © 1999 Elsevier Science B.V. All rights reserved.